The Mamlukization of the Mamluk Sultanate? State Formation and the History of Fifteenth Century Egypt and Syria: Part II — Comparative Solutions and a New Research Agenda - Steenbergen, Jo van (History compass, 2016)
This is the second of two connected articles that aim to offer a new perspective on the history of late medieval Egypt and Syria, on 15th-century political history of the so-called Mamluk Sultanate in particular. Informed by a comparative look at a selection of wider relevant scholarship, we propose to reconsider 15th-century Syro-Egyptian political action within the particular framework of a complex process of state formation. This perspective, defined as ‘Mamlukization’, may help to better account for change and for contemporary laments that "things aren't what they used to be." Part I explained how Mamluk scholarship has only recently managed to overcome a traditional tendency to view the sultanate's political history as a long process of divergence from an idealized system based on military slavery, raising new difficulties. Part II endeavors to develop an alternative perspective, inspired by scholarship that connects ways of thinking about power and politics by authors as diverse as Ibn Khaldun (d. 1406) and Pierre Bourdieu (d. 2002). This perspective makes it possible to reconsider 15th-century Syro-Egyptian political changes within the particular analytical framework of state formation, of similar patterns of political and governmental growth in late medieval and early modern Europe, and of the appearance of a new Mamluk political order.